We solve murders - Osman, Richard, 1970- (Osman, Richard, 1970- We solve murders (Series), 2024)
"Steve Wheeler is enjoying retired life. He does the odd bit of investigation work, but he prefers his familiar habits and routines: the pub quiz, his favorite bench, his cat waiting for him when he comes home. His days of adventure are over: adrenaline is daughter-in-law Amy's business now. Amy Wheeler thinks adrenaline is good for the soul. As a private security officer, she doesn't stay still long enough for habits or routines. She's currently on a remote island keeping world-famous author Rosie D'Antonio alive. Which was meant to be an easy job... Then a dead body, a bag of money, and a killer with their sights on Amy have her sending an SOS to the only person she trusts. A breakneck race around the world begins, but can Amy and Steve stay one step ahead of a lethal enemy?"--